Fuelling grammar mastery and 21st century skills through project-based learning - Mei, Fung Yong; Saad, Wan Zuhainis (Universiti Putra Malaysia, 2023)
Project-based learning (PBL) approach has been adopted in the classroom to engage students actively in the learning process and to allow them to master content knowledge and useful skills. This mixed-method study investigates the perceived benefits and challenges of using the PBL method in developing and enhancing undergraduates’ grammar mastery and 21st-century learning skills. Thirty-five ESL undergraduates from an intact grammar class participated in the study. A questionnaire was administered to elicit the participants’ views on using the PBL approach to develop grammar, collaboration, and speaking skills. In addition, group discussions on Google Docs and reflective journals were collected to obtain insights into their learning processes. The participants preferred the PBL approach, which was more effective, invigorating, and empowering than traditional lecture-style teaching. Although it was time-consuming, challenging, and rigorous, the participants demonstrated their competencies of 21st-century learning skills at the end of the project. PBL maximised language use, increased higher-order thinking, unleashed creativity, and honed ICT skills. These skills are essential to equip and prepare them to be employable and future-ready for workplace demands.